Learners’ Obstacles in the Translation of Legal Texts Between English and Vietnamese - Nhac, Thanh-Huong (International Journal of Linguistics and Translation Studies, 2023)
Legal translation, also defined as the rendering of legal texts from the source language (SL) into the target language (Cao, 2007), is deemed as one of the most rigorous translation fields due to the distinctive, culture-specific and culture-sensitive features of legal language in different law areas (Alcaraz & Hughes, 2014). Undeniably, such wide divergence has imposed great difficulties on learners and practitioners, which attracted attention from educators and scholars for the last decade. Yet, there still exists a limited number of research on this issue. Therefore, the focal aim of the present study is to investigate relevant major factors of English-majored learners’ obstacles in the process of translating legal texts between English and Vietnamese at Hanoi Law University. A mixed-method study with the utilization of survey-questionnaires, semi-structured interviews and classroom observation was employed to collect data. The results revealed the main challenges concerning linguistic aspects of legal English language, the non-equivalent legal systems and cultures, and the students’ legal background knowledge. Such findings are expected to be beneficial for both teachers and learners when it comes to learning and teaching legal translation.